Monetary Policy Variables and Economic Growth in Nigeria - Nwevo Chimezie Nwikpo (Universitas YARSI, 2022)
This study aimed to find out the impact of monetary policy variables on economic growth in Nigeria, the specific objectives were to: examine the extent to which a rise in liquidity ratio impacts economic growth in Nigeria, investigate the magnitude by which interest rate contributed to economic growth in Nigeria, and determine if an increase in the exchange rate has a significant impact on economic growth in Nigeria. The methods used in the study were unit root tests and ARDL tests. The empirical result showed liquidity ratio impacted positively on economic growth in the long run in Nigeria; interest rate impacted negatively on the economic growth in Nigeria; whereas exchange rate impacted negatively on economic growth in Nigeria. The study recommends that the Central Bank of Nigeria should ensure that deposit money banks maintained an adequate liquidity ratio that is needed for economic growth in the country. They should maintain a low and stable interest rate that will encourage investment in the country, and CBN should maintain a favorable exchange rate to attract foreign investors to invest in the country.